2020
DOI: 10.2478/aiht-2020-71-3379
|View full text |Cite
|
Sign up to set email alerts
|

The influence of specific aspects of occupational stress on security guards’ health and work ability: detailed extension of a previous study

Abstract: In our earlier study of security guards, we showed that higher occupational stress was associated with health impairments (metabolic syndrome, diabetes, hypertension, cardiovascular diseases) and work disability. The aim of this study was to further explore the association of specific occupational stressors with health impairments and work disability parameters in 399 Serbian male security guards (aged 25–65 years). Ridge linear regression analysis revealed that, after controlling for age, body mass index, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 99 publications
0
8
0
3
Order By: Relevance
“…The aim of our study was to evaluate the effectiveness of commercially available blue-light-emitting glasses, in terms of recovery need, fatigue, and related behavioural aspects, in security guards exposed to night shift work. Lower health and wellbeing levels have been reported in night security guards, including higher occurrences of occupational stress, sleep disturbances, and work-related fatigue [ 31 , 32 , 33 ]. A recent systematic review underlined the potential of bright light exposure in shift workers, but emphasized the need for more and larger randomized controlled trials [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to evaluate the effectiveness of commercially available blue-light-emitting glasses, in terms of recovery need, fatigue, and related behavioural aspects, in security guards exposed to night shift work. Lower health and wellbeing levels have been reported in night security guards, including higher occurrences of occupational stress, sleep disturbances, and work-related fatigue [ 31 , 32 , 33 ]. A recent systematic review underlined the potential of bright light exposure in shift workers, but emphasized the need for more and larger randomized controlled trials [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14] Due to the pressure and stress, large numbers of security personnel are smokers that cause high secondary impairment and diseases. [36] It is also observed that the levels of fasting glucose, total cholesterol, and blood pressure are not significantly higher in the over weighted guards. [42] A graphical representation is given that gives clear picture about the increased diastolic blood pressure and body mass index (BMI) with control [Graph 1].…”
Section: Socioeconomic Issuesmentioning
confidence: 92%
“…Hal ini akan menimbulkan stres. 17 Jurnal keenam menggunakan OSI (occupational stress index) yang dirancang oleh Dr. A.K Srivastava dan Dr. A.P Singh. Kuesioner ini diklaim bisa digunakan ke semua kategori pekerja.…”
Section: High Demandunclassified
“…Faktor tersebut mendapatkan hasil 40-60% dari skor maksimum pada skor OSI. 17 Jurnal kesembilan menyatakan hubungan antara jam kerja secara bergilir pada siang dan malam hari, dimana pekerja yang bekerja pada malam hari mengalami stres yang lebih tinggi. Hasil ini didapat dari memeriksa tingkat kortisol pada air liur dari pekerja sif malam dan sif siang.…”
Section: Pembahasan Hubungan Demand-control Dengan Stres Kerjaunclassified